Fully Mechanized Mining Technology and Practice of Water Conservation with Large Gravity Filling of Aeolian Sand-Like Paste - Pengliang Liu (Advances in Civil Engineering)
Aiming at the serious problem of Salawusu formation aquifer damage caused by caving mining in Yuyang coal mine, the technique of mechanized backfill mining with Aeolian sand-like paste was invented. Aeolian sand was used as aggregate and alkali-activated fly ash as cementing agent in the backfill material. Slurry ratio was studied where the water-sand ratio was 1 : 1.3 and the mass concentration was 72%, while slurry initial fluidity could reach 210 m. The author proposed the local resistance loss calculation method of slurry pipeline transportation, and the field gravity transport test results showed that resistance loss of unit length elbow was 4.26 times as big as loss of resistance along path; thus the pipeline diameter with 14.9 gravity of self-flowing was determined, and the pipeline flow design precision was improved by more than 10%. The backfill capacity could reach 360 m3/h and the running energy consumption was lower because of adopting backfill station model with double pulping system and underground equipment pool. The author also put forward whole backfill space sealing in which cloth consumption was only 40% of bag backfill. Industrial test showed that the backfill mining technique met requirements of water resources protection, primarily because the filling rate was 98.5% in goaf, strata behavior appeared slightly, roof water leaching was less than 2 m3/d, and surface subsidence value was only 38 mm. There were great breakthroughs in cost and production efficiency in this technology compared with similar technologies.